Cytokines and autoimmune diseases - Kuchroo, Vijay K; Ed. Hafler, David A; Ed (Humana Press, 2002)
Although the role of cytokines and chemokines in the induction and regulation of autoimmunity has a vast current literature, there is as yet no clear consensus about the details of this complex process. In Cytokines and Autoimmune Diseases, leading researchers synthesize the available information to help develop an intimate understanding of how cytokines and chemokines are involved in the pathogenesis of autoimmune diseases. The many chapters offer critical reviews of the basic mechanisms controlling cytokine induction and regulation, as well as the resulting production of proinflammatory and anti-inflammatory cytokines, the former of which induces organ-specific autoimmune diseases. From the vantage of these insights, they address the role of cytokines in a wide variety of autoimmune disease, uvetis, encephalomyelitis, multiple sclerosis, human type 1 diabetes, rheumatoid arthritis, SLE, and myasthenia gravis. Authoritative and state-of-the-art, Cytokines and Autoimmune Diseases comprehensively integrates the diffuse literature of this dramatically advancing field, and highlights the enormous therapeutic potential of cytokine modulation in the treatment of autoimmune disease.